Racial differences in attitudes to clinical pig organ Xenotransplantation. (25th October 2020) - Padilla, Luz A.; Hurst, Daniel J.; Jang, Kyeonghee; Rosales, Johanna R.; Sorabella, Robert A.; Cleveland, David C.; Dabal, Robert J.; Cooper, David K.; Carlo, Waldemar F.; Paris, Wayne
Abstract: Introduction: In addition to an organ donor shortage, racial disparities exist at different stages of the transplantation process. Xenotransplantation (XTx) could alleviate these issues. This study describes racial differences in attitudes to XTx among populations who may need a transplant or are transplant recipients. Methods: A Likert‐scale survey was distributed at outpatient clinics to parents of children with congenital heart disease (CHD) and kidney patients on their attitudes to pig organ XTx. Data from these two groups were stratified by race and compared. Results: Ninety‐seven parents of children with CHD (74.2% White and 25.8% Black) and 148 kidney patients (50% White and 50% Black) responded to our survey. Black kidney patients' acceptance of XTx although high (70%) was lower than White kidney patients (91%; P .003). White kidney patients were more likely to accept XTx if results are similar to allotransplantation (OR 4.14; 95% CI 4.51‐11.41), and less likely to be concerned with psychosocial changes when compared to Black kidney patients (receiving a pig organ would change your personality OR 0.08; 95% CI 0.01‐0.67 and would change social interaction OR 0.24; 95% CI 0.07‐0.78). There were no racial differences in attitudes to XTx among parents of children with CHD. Conclusion: There are differences in attitudes to XTx particularly among Black kidney patients. Because kidneys may be the first organ for clinical trials of XTx, future studies that decrease scientific mistrust and XTx concerns among the Black community are needed to prevent disparities in uptake of possible future organ transplant alternatives.